Możliwości rozwojowe przemysłu spożywczego w województwie warmińsko-mazurskim - Menart, Łukasz; Juchniewicz, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main aim of this article was to estimate potential and development prospects of food industry in Warmia and Mazury. To estimate those features, location quotient and shift-share analysis were used. Variables analyzed in the paper were number of enterprises, value of sold production, and employment in province's food industry in comparison with whole country. Research results showed that food manufacturing has weak prospects of development. It needs careful analysis of reasons for decrease of food industry's potential in warmińsko-mazurskie voivodship. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 274-280